2020
DOI: 10.3389/fonc.2020.00810
|View full text |Cite
|
Sign up to set email alerts
|

Non-Coding RNAs Operate in the Crosstalk Between Cancer Metabolic Reprogramming and Metastasis

Abstract: Metastasis, the spread of cancer cells from a primary tumor to a secondary site, represents one of the hallmarks of malignancies and the leading cause of cancer-related death. The process of metastasis is a result of the interaction of genetic heterogeneity, abnormal metabolism, and tumor microenvironments. On the other hand, metabolic reprogramming, another malignancy hallmark, refers to the ability of cancer cells to alter metabolic and nutrient acquisition modes in order to support the energy demands for ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 135 publications
0
21
0
Order By: Relevance
“…As ncRNAs were initially considered to lack biological function because they do not encode proteins, they play a role in cancer progression by regulating enzymes and pathways involved in the metabolic reprogramming of cancer cells. This regulation primarily occurs through glucose, glutamine, and lipid metabolism and involves two types of ncRNA, long-chain non-coding RNA (lncRNA) and microRNA (miRNA) [ 154 ].…”
Section: Role Of Non-coding Rnas In Cancer Cell Metabolismmentioning
confidence: 99%
See 2 more Smart Citations
“…As ncRNAs were initially considered to lack biological function because they do not encode proteins, they play a role in cancer progression by regulating enzymes and pathways involved in the metabolic reprogramming of cancer cells. This regulation primarily occurs through glucose, glutamine, and lipid metabolism and involves two types of ncRNA, long-chain non-coding RNA (lncRNA) and microRNA (miRNA) [ 154 ].…”
Section: Role Of Non-coding Rnas In Cancer Cell Metabolismmentioning
confidence: 99%
“…There are several enzymes related to glucose metabolism that are regulated by ncRNAs in cancer. HK2 expression, for example, is downregulated by miR-199a-5p and miR-125b, with lower expression of these ncRNAs corresponding with enhanced growth [ 154 ]. In breast cancer, GLUT1 and PK expression are downregulated by the secretion of vesicles containing miR-122, which decreases glucose uptake in non-tumor cells to increase nutrient availability in pre-metastatic cells and promote metastasis [ 156 ].…”
Section: Role Of Non-coding Rnas In Cancer Cell Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…Short 18–22 base pair long endogenous miRNAs play a key role in controlling gene expression by regulating several physiological, but also pathological processes, including carcinogenesis [ 81 ]. In addition, miRNAs have been identified as participating in the regulation of metabolic remodulating [ 82 ]. In this context, a number of hypoxia and HIF-dependent miRNAs with oncogenic and/or suppressive functions in cancer development were summarized [ 80 , 83 , 84 , 85 ].…”
Section: Micrornas Involved In the Metabolic Alterations Of Osccmentioning
confidence: 99%
“…Emerging evidence has demonstrated that long non-coding RNAs (lncRNAs) display diverse cellular functions and widely participate in both physiological and pathophysiological processes ( Li and Sun, 2020 ; Sayad et al, 2020 ; Zhang et al, 2020 ). LncRNAs are a diverse class of RNA transcripts longer than 200 nucleotides that have limited protein coding capacity ( Zhou et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%